2003
DOI: 10.1002/ijc.11243
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drug‐induced apoptotic death on processing and presentation of tumor antigens by dendritic cells

Abstract: Here we have studied the effects of apoptotic cell death induced by chemotherapic agents on tumor phagocytosis by dendritic cells (DC) and presentation of the relevant antigen to T lymphocytes. Annexin-V-FITC (Ann-V) and propidium iodide (PI) staining was used to assess early apoptotic (Ann-V ؉ /PI ؊ ) vs. late apoptotic/secondary necrotic (Ann-V ؉ /PI ؉ ) death after a 24 hr observation of untreated and drug-treated gastric carcinoma cells. After treatments, the HLA-A*0201 ؉ tumor cell line KATO III was expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 30 publications
2
47
0
Order By: Relevance
“…Pioneering studies showed that 5-FU and doxorubicin induced in vitro cancer expression of heat shock proteins (HSPs) that promote the engulfment of cell debris by human DCs and the subsequent crosspresentation of tumor antigens to T-cells. 29,30 More recently, Casares et al 31 showed that doxorubicin-killed tumor cells elicit tumor-specific immune responses when injected into syngeneic mice, by stimulating DC phagocytosis and CD8 T-cell responses. Subsequent work from L. Zitvogel's laboratory identified the molecular mechanism linking immunogenic apoptosis induced by chemotherapy to DC activation, as detailed below.…”
Section: Effects On the Innate Immune Systemmentioning
confidence: 99%
“…Pioneering studies showed that 5-FU and doxorubicin induced in vitro cancer expression of heat shock proteins (HSPs) that promote the engulfment of cell debris by human DCs and the subsequent crosspresentation of tumor antigens to T-cells. 29,30 More recently, Casares et al 31 showed that doxorubicin-killed tumor cells elicit tumor-specific immune responses when injected into syngeneic mice, by stimulating DC phagocytosis and CD8 T-cell responses. Subsequent work from L. Zitvogel's laboratory identified the molecular mechanism linking immunogenic apoptosis induced by chemotherapy to DC activation, as detailed below.…”
Section: Effects On the Innate Immune Systemmentioning
confidence: 99%
“…To induce apoptosis in Kato cells, we incubated the cells for 24 h with 100 lg/mL cisplatin according to a protocol established by Buttiglieri et al [45]. The nonadherent apoptotic Kato cells were recovered and washed three times to remove the cisplatin, and approximately 500 000 apoptotic Kato cells were incubated with 100 000 monocytes or 50 000 B cells.…”
Section: Generation and Use Of Apoptotic Kato Cellsmentioning
confidence: 99%
“…Similar to the inflammatory response to pathogens, sterile inflammation is marked by apoptosis and/or necrosis of an enormous number of cells in different organs and tissues [1]. These dead or dying cells release a large repertoire of endogenous ligands, such as nucleic acids, heat shock proteins, uric acid and intracellular proteins, which can bind to pattern recognition receptors on leukocytes, particularly those on dendritic cells and macrophages, and initiate inflammation, tissue injury and adaptive immune responses [3][4][5][6][7][8]. In infections, the inflammatory response is usually limited because the microbes are often rapidly cleared by humoral and/or cellular immune mechanisms.…”
Section: Sterile Inflammationmentioning
confidence: 99%
“…This forms the basis for the induction of peripheral tolerance, which is required in addition to the central tolerance acquired during the early days of development of the immune system. In response to pathogens or products of tissue injury, the DCs in tissues undergo maturation and increase their expression of antigen presentation and co-stimulatory molecules and production of cytokines and chemokines, which are required to initiate inflammatory innate or adaptive immune responses [3,4,6,17].…”
Section: Dendritic Cells In Immunity and Tolerancementioning
confidence: 99%